2014
DOI: 10.1186/1756-6606-7-36
|View full text |Cite
|
Sign up to set email alerts
|

Block of T-type calcium channels by protoxins I and II

Abstract: BackgroundLow-voltage-activated (T-type) calcium channels play a crucial role in a number of physiological processes, including neuronal and cardiac pacemaker activity and nociception. Therefore, finding specific modulators and/or blockers of T-type channels has become an important field of drug discovery. One characteristic of T-type calcium channels is that they share several structural similarities with voltage-gated sodium channels (VGSCs). We therefore hypothesized that binding sites for certain sodium ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 34 publications
1
35
1
Order By: Relevance
“…Both peptides were subsequently shown to block Ca V 3 channels in a subtype-dependent manner (Edgerton et al, 2010). Protoxin I preferentially blocks Ca V 3.1 channels over Ca V 3.3 and even more so over Ca V 3.2 (Ohkubo et al, 2010;Bladen et al, 2014b). Protoxin II appears to act as a gating modifier, with the highest affinity for Ca V 3.2 channels (Edgerton et al, 2010;Bladen et al, 2014b).…”
Section: Ca V 3 Channel Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Both peptides were subsequently shown to block Ca V 3 channels in a subtype-dependent manner (Edgerton et al, 2010). Protoxin I preferentially blocks Ca V 3.1 channels over Ca V 3.3 and even more so over Ca V 3.2 (Ohkubo et al, 2010;Bladen et al, 2014b). Protoxin II appears to act as a gating modifier, with the highest affinity for Ca V 3.2 channels (Edgerton et al, 2010;Bladen et al, 2014b).…”
Section: Ca V 3 Channel Pathophysiologymentioning
confidence: 99%
“…Protoxin I preferentially blocks Ca V 3.1 channels over Ca V 3.3 and even more so over Ca V 3.2 (Ohkubo et al, 2010;Bladen et al, 2014b). Protoxin II appears to act as a gating modifier, with the highest affinity for Ca V 3.2 channels (Edgerton et al, 2010;Bladen et al, 2014b). Another spider toxin that blocks T-type calcium channels is PsPTx3, a peptide isolated from Theraphosidae tarantula that has apparent selectivity for Ca V 3.2 calcium channels (French patent application FR2940973).…”
Section: Ca V 3 Channel Pathophysiologymentioning
confidence: 99%
“…L-and T-type calcium channels are the two major forms of calcium channels within the cell [67]. Several natural peptides have been identified that target these calcium channels [68,74]. In addition to these natural peptides, there is also a range of synthetic calcium channel binding compounds that have been developed by the pharmaceutical industry that may be used as targeting compounds.…”
Section: Calcium Channelsmentioning
confidence: 99%
“…Off-target activity may occur within channels or receptors of the same class due to high sequence homology or it may occur within different ion channel or receptor classes due to structural homology. Promiscuous activity is particularly evident amongst venom-derived peptides that target the voltage-sensing domain of voltage-gated ion channels, with venom-derived peptides from spiders often reported to have activity at NaV, KV and CaV channels [16,65,132,164]. However, it should be noted that compared to most other probes, including synthetic small molecules and endogenous ligands, toxins in general remain to be the most selective modulators available for voltage-gated and ligand-gated ion channels.…”
Section: Limitations Of Using Toxins As Probesmentioning
confidence: 99%